2008
DOI: 10.1109/jqe.2008.922322
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Comparison of Injection-Seeded and Self-Seeded Performance of a 1060-nm Gain-Switched Fabry–PÉrot Laser Diode

Abstract: Abstract-We investigate and compare the performance of a gain-switched picosecond Fabry-Pérot laser diode operated at 1.06 m under both injection-and self-seeded conditions. Our experiments show that comparable performance can be obtained for both modes of operation, with the self-seeding arrangement offering overall benefits in terms of reduced system complexity and cost, providing the associated quantization of available pulse repetition rate can be tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…While the demonstrated source exhibited pulse-to-pulse fluctuations as per the nature of the gain-switched diode seed, the observed energy jitter was already low enough to be acceptable for many applications. Further noise reductions might be accomplished by self-seeding [89,132,133] or injection seeding [134,135] the diode, although the former sacrifices fine control over the gainswitched diode's repetition rate. Additional Mamyshev regenerators could be added in sequence in order to effect a more stepwise transfer function and funnel the pulses towards a uniform eigenstate [50,51].…”
Section: Prospects For Short Pulses Without Mode-locking: Multi-stagementioning
confidence: 99%
“…While the demonstrated source exhibited pulse-to-pulse fluctuations as per the nature of the gain-switched diode seed, the observed energy jitter was already low enough to be acceptable for many applications. Further noise reductions might be accomplished by self-seeding [89,132,133] or injection seeding [134,135] the diode, although the former sacrifices fine control over the gainswitched diode's repetition rate. Additional Mamyshev regenerators could be added in sequence in order to effect a more stepwise transfer function and funnel the pulses towards a uniform eigenstate [50,51].…”
Section: Prospects For Short Pulses Without Mode-locking: Multi-stagementioning
confidence: 99%
“…Gain-switched or mode-locked optical pulses of low timing jitter are very useful for high-speed optical time-division multiplexed communications and all-optical signal processing. It has been demonstrated previously that the timing jitter of gain-switched semiconductor lasers, such as Fabry-Perot (FP) LDs and distributed feedback (DFB) LDs, could be reduced by an external laser beam injection [17,18]. However, it was observed that a trade-off relationship existed between the jitter reduction and pulse width shortening of the gain-switched LDs.…”
Section: Timing-jitter Reduction Of Gain-switched Single-mode Vcselsmentioning
confidence: 99%
“…We furthermore measure the single-pulse spectra using the dispersive Fourier transform technique [26], and confirm that the distributions of the pulses and their energies are not heavytailed, nor are the averages strongly skewed by extreme outliers (see Appendix B). Finally, techniques such as self-seeding [27][28][29] and external injection [30,31] have been thoroughly investigated as ways of curtailing shot-to-shot fluctuations in GSDs, reducing timing jitter, or even creating interpulse coherence [32]. We expect that implementing these approaches in a similar system to ours will yield comparable noise reductions, making such systems viable alternatives to modelocked oscillators even for noise-or coherencesensitive applications.…”
mentioning
confidence: 95%